2(1+7x)-3(x-3)=+55

Simple and best practice solution for 2(1+7x)-3(x-3)=+55 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 2(1+7x)-3(x-3)=+55 equation:


2(1+7x)-3(x-3)=+55

We simplify the equation to the form, which is simple to understand
2(1+7x)-3(x-3)=+55

Reorder the terms in parentheses
+(+2+14x)-3*(x-3)=+55

Remove unnecessary parentheses
+2+14x-3+*(+x-3+)=+55

Reorder the terms in parentheses
+2+14x+(-3x+9)=+55

Remove unnecessary parentheses
+2+14x-3x+9=+55

We move all terms containing x to the left and all other terms to the right.
+14x-3x=+55-2-9

We simplify left and right side of the equation.
+11x=+44

We divide both sides of the equation by 11 to get x.
x=4

See similar equations:

| 2x+5=-75+8x | | 2x+5=20-x | | -18-9m=m^2 | | 6x+22=14x-17 | | 1/3-40.90 | | 5x+30=10x+40 | | 40.90-1/3 | | 13x^2+11x-24=0 | | -7(8k-4)-7(k-6)=7 | | -7(8k-4)-7(k-6)= | | 3x+1/2-x=6x-4/7 | | y+3=-1/5(x-6) | | -4x+4x=11-4-2-5 | | x+4/3y=-5 | | 289=256x^2+81x^2 | | r^2-7r=8 | | 6.8(x-1)=-0.2x+42.2 | | (30x^3)=0 | | (30x^2)=0 | | 30x^2=0 | | (30x^4)=0 | | x^2+54x+728=0 | | +12-13=45+12 | | x^2+54x+727=0 | | (30x^4)(x-1)=0 | | x^2+441-21x+x^2=225 | | 13+3a=5+24 | | 13x/2+14=40 | | X/7+14=28 | | 8x/3+35=59 | | 2x^2-21x+216=0 | | X/4+10=100 |

Equations solver categories